2007
DOI: 10.2511/rpsd.32.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Review of Studies with Students with Significant Cognitive Disabilities Which Link to Science Standards

Abstract: A comprehensive review of research was conducted on teaching science to students with significant cognitive disabilities. Guidelines from the National Science Education Standards were used to identify categories of studies based on the strands of science. A total of 11 studies were identified from the 20 years of literature searched. In general, work in the area of science is sparse for students with significant cognitive disabilities. Eight of the 11 studies fell in Content Standard F: Science in Personal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 10 publications
2
85
1
Order By: Relevance
“…While research on language arts and mathematics is limited for students with severe disabilities, research in the area of science is especially sparse. Courtade et al (2007) found a limited number of studies in whieh science content was taught to students with severe disabilities. For example, a search of the literature using key terms from the NSES (NAS, 1996) revealed 11 studies in which some science content (e.g., weather words, first aid skills) was taught to this population.…”
Section: Science For Students With Severe Disabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…While research on language arts and mathematics is limited for students with severe disabilities, research in the area of science is especially sparse. Courtade et al (2007) found a limited number of studies in whieh science content was taught to students with severe disabilities. For example, a search of the literature using key terms from the NSES (NAS, 1996) revealed 11 studies in which some science content (e.g., weather words, first aid skills) was taught to this population.…”
Section: Science For Students With Severe Disabilitiesmentioning
confidence: 99%
“…Unfortunately, the small research base on teaehing science to students with severe disabilities has only a few examples of using an inquiry base or even teacbing concepts. Instead, most of the researcb has been either completing a daily living skill (e.g., first aid) or recognizing vocabulary (e.g., weather words; Courtade et al, 2007). As in math and language arts, in science, educators will need to apply proeedures proven effective in other content to new grade-appropriate objectives.…”
Section: Science For Students With Severe Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing attention has been drawn to the role of technology in special education to apply inquiry-based instruction and project-based instruction with Special Needs Students (Courduff, Szapkiw, & Wendt, 2016;Courtade, Spooner, & Browder, 2007;Ke et al, 2015;Regan et al, 2014). The Journal of Learning Disabilities had a special issue (1998, vol.…”
Section: Technology-rich Science Education For Special Needs Studentsmentioning
confidence: 99%
“…2; Several instruction methods, such as video self-models for teaching concepts such as prepositions (Mechling & Hunnicutt, 2011) and simultaneous prompting for teaching object naming, in a group format or pull-in strategy in inclusive settings (Tekin-Iftar et al, 2008), and constant time delay for teaching grade-level core content (i.e., heredity) for adolescents with moderate or severe intellectual disabilities were recommended (Riggs et al, 2013). Inquiry in science lessons can also be taught to students with moderate to severe intellectual disabilities with task analytic instruction, and teachers should target the generalization of these skills (Courtade et al, 2007).…”
Section: Curriculum and Instructionmentioning
confidence: 99%